Rede de drenagem e sistema viário da bacia do Rio Turvo Sujo - Ferreira Valente , Osvaldo; Ribeiro , José Carlos; de Paula Neto , Francisco (Revista Ceres, 2025)
This paper describes the preparation of a planimetric map of the watershed of the Rio Turvo Sujo, showing the drainage, petwork and road system.